Proceedings of the 2nd International Workshop on Multimedia Privacy and Security 2018
DOI: 10.1145/3267357.3267370
|View full text |Cite
|
Sign up to set email alerts
|

Online Tracking of Kids and Teens by Means of Invisible Images

Abstract: The recent news of a large-scale online tracking campaign involving Facebook users, which gave way to systematic misuse of the collected user-related data, has left millions of people deeply concerned about the state of their online privacy as well as the state of the overall information security in the cyber world. While most to-date revelations pertaining to user tracking are related to websites and social media generally intended for adult online users, relatively little is known about the prevalence of onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Senzing Inc. [14] suggests that around 60% of European companies are not yet prepared for GDPR and 44% of the EU's larges companies are worried about compliance with GDPR. [18] studies kids and teenagers' privacy and finds the EU children may be subject to more third party tracking compared to the US. [8] examines news websites and finds that UK in particular has a high level of tracking.…”
Section: Related Workmentioning
confidence: 99%
“…Senzing Inc. [14] suggests that around 60% of European companies are not yet prepared for GDPR and 44% of the EU's larges companies are worried about compliance with GDPR. [18] studies kids and teenagers' privacy and finds the EU children may be subject to more third party tracking compared to the US. [8] examines news websites and finds that UK in particular has a high level of tracking.…”
Section: Related Workmentioning
confidence: 99%
“…COPPA disallows certain data collection practices, as well as requiring parental consent. Further, it prohibits having targeting advertisements (Vlajic et al, 2018). The study Reyes et al (2018) revealed that the majority of the free children's apps potentially are violating COPPA.…”
Section: Regulations and Children Right'smentioning
confidence: 99%
“…GDPR aims to provide guidance in privacy and data protection and improve scientific integrity of human-related studies. GDPR has a broader focus than COPPA and is written to be a flexible legal framework that can be customized further by the countries in the EU (Vlajic et al, 2018). However, it is as strong as COPPA regarding the protection of children's privacy online.…”
Section: Regulations and Children Right'smentioning
confidence: 99%
“…Among other things, this information will be used to make business decisions, to create consumer profiles or behavioural trends. Furthermore, Vlajic et al ( 2018 ) argue that this type of tracking, in terms of user privacy, can be considered a major risk, because it could lead to the extraction and leakage of sensitive personal data. But it is also related to other ethical issues such as weblining [a practise that makes a user ineligible for certain goods and services based on their online profile] because, although today there is the possibility of creating anonymous avatars, with the increasing development of technology, it is very likely that, in the future, the anonymous digital avatar can be linked to the real person and their real-life transactions (Corcoran and Costache, 2018 ).…”
Section: Introductionmentioning
confidence: 99%